ASSESSMENT OF ANTIISCHEMIC AND ANTIANGINAL EFFECTS OF NICORANDIL BY TREADMILL TEST, UNDER THE FRAMEWORK OF KVAZAR STUDY - V. P. Voronina; S. Yu. Martsevich; N. P. Kutishenko; A. D. Deev (Российский кардиологический журнал)
Aim. Under the framework of KVAZAR study, to assess antianginal and antiischemic effects of nicorandil therapy with exercise test on treadmill in chronic coronary heart disease patients (CCHD) with stable angina.Material and methods. Randomized, double blind, placebo-control study, conducted in 2 parallel groups,  multicenter. Totally, 120 patients included, all were taking metoprolol tartrat 50 mg b.i.d. After randomization, main group was added nicorandil 10 mg b.i.d., in 2 weeks the dosage was increased to 20 mg b.i.d., control took placebo.  Duration of the  study  6 weeks.  For the  evaluation  of efficacy of nicorandil therapy 10-20 mg b.i.d., exercise  test was used,  done at randomization visit (V0) and in 6 weeks (V6).Results. Intake of nicorandil, in 6 weeks was followed by a significant increase of the time before  the onset  of angina (p<0,0001),  time to ST depression appearance for 1 mm (p<0,005)  and time for angina attack of moderate severity development  (p<0,005).  In placebo  group,  only the  angina  onset  tolerance  parameter improved  (p<0,01),  but duration of exercise test and time for ST depression 1 mm did not change significantly. In the subgroup  of patients  having ischemic  ECG changes during exercise  test,  it was showed significant increase of these  changes in nicorandil vs placebo  (p<0,05); which confirms the anti-ischemic action of nicorandil during the day in double dosing regimen. Conclusion. Nicorandil did statistically  significantly improve  the  parameters of exercise  tolerance  in CCHD patients  with stable  angina.  The results  of the study make it to conclude  on the additional and clinically significant impact of the drug 10-20 mg b.i.d. as an effective antianginal medication of  second-line therapy for treatment of patients with CCHD with stable angina.